The dollar-mark axis : on currency power - Brown, Brendan (New York : St. Martin's Press, 1979)
This paper provides a comprehensive analysis of the determinants of the dollar-mark axis. It shows that while financial factors affect the dollar/mark exchange rate, other factors such as monetary policy or the trade structure determine how currencies react to a given change in the dollar/mark rate. Also the main findings of the empirical work suggest that exchange rate policy, trade links and international portfolio bias are the principal determinants of the dollar-mark axis.
Includes index.
Includes bibliographies
usc 25/05/18
Loans
Keywords: International finance; Currency question; Money market